Experimental study on CO2 flooding/huff and puff of medium-deep heavy oil in Xinjiang Oilfield - SHI Yan, XIE Junhui, GUO Xiaoting, WU Tong, CHEN Dequan, SUN Lin, DU Daijun (Youqicang pingjia yu kaifa)
Addressing the challenges of moderate to strong velocity sensitivity damage and strong to extremely strong water sensitivity damage in the medium and deep heavy oil reservoirs of Xinjiang oilfields, which lead to suboptimal waterflooding outcomes, a study was conducted leveraging the unique physical and chemical properties of CO2. Utilizing high-temperature, high-pressure PVT apparatus and long core displacement equipment, the feasibility of enhancing oil recovery through CO2 flooding/huff and puff was explored by determining the high-pressure physical properties of CO2-crude oil and analyzing the composition and viscosity changes of the produced oil with gas chromatography and high-temperature, high-pressure rheometry. The experimental results show that 57.345% mole fraction of CO2 can increase the dissolved gas-oil ratio（GOR） from 32 m3/m3 to 149.3 m3/m3, the bubble point pressure（pb） from 6.8 MPa to 15.7 MPa, the volume coefficient of crude oil from 1.06 to 1.27, the density of crude oil from 0.896 5 g/cm3 to 0.854 8 g/cm3, and the viscosity of crude oil from 419.3 mPa·s to 253.4 mPa·s. Therefore, CO2 can effectively supplement the formation energy, increase the elastic energy of crude oil and reduce the seepage resistance. The first round of 0.95 PV（pore volume） CO2 flooding has a crude oil recovery of 32.8%, and the fluid in the porous medium is redistributed after 24 hours of shut-in. The second round of 0.5 PV CO2 flooding can increase the crude oil recovery by 17.9%. The crude oil recovery of five rounds of CO2 huff and puff is 63.5%. The viscosity of the produced oil tends to decrease, mainly due to the deposition of asphaltenes in crude oil in porous media. The experimental results have confirmed the feasibility of CO2 flooding/huff and puff in the recovery of heavy oil in the middle and deep layers of Xinjiang Oilfield.